Scriptus Propertius: Propertius between Body and Text. - Fredericksen, Erik (Helios)
This article traces how Propertius imagines being read, and argues that problems surrounding the representation of his male body underlie conflicting anxieties of authorship. It begins by suggesting that a number of funereal scenes allow Propertius to figure his own absence in future readers' interactions with his poetry and express his lack of control over the reception of his text. At the same time, though, this epitaphic model of reading protects his body from his readers' aggressive gaze. In fact, Propertius continually deflects visual focus from his body throughout his poetry, and is wary of inscribing his body into his text and becoming a textual-bodily object like Cynthia. Finally, the article examines occasions when Propertius is marked with a nota. These scenes allow Propertius to envision the threat of textual objectification he elsewhere avoids, and express anxieties about what it means to be read. Drawing on the ways in which Propertius's elegies display and conceal his body, the article claims that this poetry, so concerned with literary immortality and poetic fame, also evidences a deep—and gendered—ambivalence toward becoming an object to be read.